2022
DOI: 10.1111/cote.12612
|View full text |Cite
|
Sign up to set email alerts
|

The roles of polymer relaxation phenomena, aqueous dye solubility and the physical properties of water in the mechanism of adsorption of a disperse dye on poly(ethylene terephthalate) fibres: Part 2 dye solubility

Abstract: The marked temperature‐dependent uptake of a commercial disperse dye on poly(ethylene terephthalate) fabric achieved during an aqueous high temperature dyeing process is the likely amalgamation of at least two separate, but intrinsically inter‐related, thermally activated processes, namely, poly(ethylene terephthalate) structural relaxations, as articulated in terms of polymer chain segmental mobility and available free volume, in which glass transition adopts a principal role, as well as disperse dye aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(57 citation statements)
references
References 51 publications
7
45
0
Order By: Relevance
“…However, as mentioned, the results obtained for the commercial dye Teratop Yellow HL‐G 150%/PET fabric presented in the previous part of the paper 2 clearly showed that the aqueous solubility of the dye adopts a very important mechanistic role in the aqueous HT dyeing process employed. From this, it follows that despite the innate hydrophobicity of both PET fibres and disperse dyes, water must undertake fundamentally important functions in aqueous, HT dyeing processes.…”
Section: Poly(ethylene Terephthalate) Fibresmentioning
confidence: 82%
See 4 more Smart Citations
“…However, as mentioned, the results obtained for the commercial dye Teratop Yellow HL‐G 150%/PET fabric presented in the previous part of the paper 2 clearly showed that the aqueous solubility of the dye adopts a very important mechanistic role in the aqueous HT dyeing process employed. From this, it follows that despite the innate hydrophobicity of both PET fibres and disperse dyes, water must undertake fundamentally important functions in aqueous, HT dyeing processes.…”
Section: Poly(ethylene Terephthalate) Fibresmentioning
confidence: 82%
“…As previously discussed, 2 the structure of liquid water (eg 3–7 ) is of major significance in all exhaust dyeing processes 8–11 in view of the manifold, but inherently complex, interactions that this most exquisite of solvents undertakes with each of the many, varied dyebath components (eg, dye molecules, fibre macromolecules, dispersing agents, buffers and levelling agents, etc. ).…”
Section: Watermentioning
confidence: 99%
See 3 more Smart Citations